Impression Management Komunitas Role player K-POP dalam Media Sosial Twitter - Rienadhy, Anindya Cindy Dama (Universitas Brawijaya, 2022)
The emergence of K-Pop in Indonesia has given rise to a rapidly evolving fan culture on various social media platforms, one of which is Twitter. Fandom communities on Twitter have, in turn, brought forth a new phenomenon: the emergence of K-Pop Roleplayer communities. K-Pop Roleplaying involves participants assuming the personas of Korean celebrities as characters in their interactions. Since players essentially 'borrow' the identities of others in this game, terms like